The scope of the Sunna in Shafi'is thought system - Kutluay, İbrahim (SILA SCIENCE, 2012)
Shafi'i was the first jurist to define sunna as the model behavior of the Prophet, in contrast with his predecessors, who thought that the idea was not necessarily connected with the Prophet, but represented the traditional, albeit ideal, usage of the community, forming their "living tradition" on an equal footing with customary or general agreed practice. Shafi'i was not only a master in the knowledge of hadith or fiqh, but he was also well versed in Arabic linguistics, poetry, and genealogy. In fact, what earned Shafi'i the title of 'the revivalist' of the second century was that he was the one who put the fundamentals of jurisprudence (usul al-Fiqh). Scholars before him used to gather the ahadith that were commonly known in their countries, and when a hadith seemed in contradiction with another, they used their personal judgement to decide which one is the most acceptable. Then at the time of Shafi'i, the Prophet's ahadith were gathered from different countries, and thus the disagreements among the scholars increased as well, until Shafi'i wrote his famous book, al-Risala, which is considered to be the foundation of Islamic jurisprudence. Basically Shafi'i relied on the literal meaning of the Qur'an, then on the authentic Sunnah. He was the first to distinguish and separate between the application of discretion in legal matters (istihsan), and the juristic reasoning by analogy (qiyas). This paper, therefore, focuses on the scope and status of the Sunna in al-Shafii's thought system by taking into consideration his own works, particularly al-Risala and al-Umm.
Keywords: Al-Shafi'i; Sunna; Al-Risala; ijtihad; Qiyas